2010
DOI: 10.1016/j.jvs.2009.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Isopropylamine NONOate (IPA/NO) moderates neointimal hyperplasia following vascular injury

Abstract: Objective Isopropylamine NONOate (IPA/NO) is a nitroxyl (HNO) donor at physiological pH. HNO is a positive inotrope and vasodilator, but little is known about its effect on neointimal hyperplasia. The aims of this study are to determine the effect of IPA/NO on endothelial and vascular smooth muscle cells (VSMC) in vitro, and to determine if IPA/NO inhibits neointimal hyperplasia in vivo. Methods VSMC were harvested from the abdominal aortas of male Sprague Dawley rats, and human umbilical vein endothelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…Once anesthetized, as evident by absence of response to toe pinch, the animals were euthanized via a bilateral thoracotomy. The aortas were removed, and the cells were isolated and maintained as previously described (30). Briefly, after the aorta is removed, the endothelial layer is gently removed by scraping.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once anesthetized, as evident by absence of response to toe pinch, the animals were euthanized via a bilateral thoracotomy. The aortas were removed, and the cells were isolated and maintained as previously described (30). Briefly, after the aorta is removed, the endothelial layer is gently removed by scraping.…”
Section: Methodsmentioning
confidence: 99%
“…All animal procedures were performed in accordance with the Guide for the Care and Use of Laboratory Animals published by the National Institutes of Health (NIH Publication 85- 23,1996) and approved by the Northwestern University Animal Care and Use Committee. Thirty 11-wk-old male Sprague Dawley rats weighing between 350 and 400 g underwent the carotid artery balloon injury model, as previously described (17,28,30). Animals were anesthetized with isoflurane (1.5-5%) and treated preoperatively with carprofen subcutaneously (0.15 mg/kg) for pain control.…”
Section: Methodsmentioning
confidence: 99%
“…Studies in support of preserved vascular actions of HNO under pathophysiological conditions include the finding that Angeli's salt-mediated inhibition of ADP-stimulated platelet aggregation was sustained in patients with sickle cell disease (21). IPA/NO has also been shown to limit neointimal hyperplasia in rats (29), and Paolocci and colleagues (22) have indirectly shown that the hemodynamic actions of HNO are sustained in acute experimental heart failure. However, it remains unclear whether HNO donors offer advantages over traditional nitrovasodilators, such as GTN, in the treatment of vascular diseases where there is increased generation of ROS such as O 2 ·Ϫ and reduced NO • signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Angeli's salt has been shown to lower blood pressure in the setting of acute experimental heart failure (22) and inhibit the aggregation of platelets from patients with sickle cell disease (21). In addition, IPA/NO has been reported to limit neointimal hyperplasia in rat carotid arteries after balloon injury (29).…”
mentioning
confidence: 99%
“…Importantly, we have shown that, unlike clinically used nitrovasodilators such as GTN, vascular tolerance to HNO donors does not develop either in vitro (5,11) or in vivo (12) with continued use. In addition, the vasodilatory capacity of HNO is accompanied by an ability of this nitrogen oxide to inhibit platelet aggregation (5, 21) and limit vascular smooth muscle proliferation (30).…”
mentioning
confidence: 99%